The Effect of Dividend Policy on Changes in the Stock Value of Banking Companies in the IDX30 Index in 2022 - Madiistriyatno, Harries; Julioni, Heny; Listiorini, Dewi (Raudhah Publisher, 2024)
The use of financial technology is currently continuing to grow with various feature Which available. Convenience Which offered become factor the occurrence growth in interest of financial technology users despite the risks involved obtained. Study This aiming know Influence Perception Convenience And Risk To Interest Use Financial Technology ( Fintech) on Generation Z of Galajuara Vocational High School, Bekasi City. Using quantitative methods with data collection through questionnaire distribution. Based on the results of data analysis And discussion, in a way partial perception convenience influential significant positive to interest use financial technology with t count 7,274  t table 2,001 with level significance 0.00  0.05, mark coefficient as big as 0.478 It means variable Perception of ease of use has a strong relationship with intention to use financial technology . Risk in a way partial influential significant negative to interest in using financial technology with a calculated t of 3.749 t table 2.001 with significance level 0.00 0.05, coefficient value of 0.118 means the risk variable has a strong relationship with interest in using financial technology . Together, perceptions of convenience and risk influence interest use financial technology with F count 29,285  F table 3.15 with level significance 0.00 0.05.